Dielectric, mechanical, and microstructural characterization of HA–BST composites. (July 2015) - Inthong, S.; Tunkasiri, T.; Rujijanagul, G.; Pengpat, K.; Kruea-In, C.; Intatha, U.; Eitssayeam, S.
Abstract: Hydroxyapatite (HA) is an excellent inorganic biomaterial and has various applications because its structure is similar to the inorganic matrix of human bone and dental enamel. In this present study, the HA–(Ba0.7 Sr0.3 )TiO3 ; HA–BST composites were synthesized by a solid state reaction technique. The phase, densification, microstructure, mechanical and dielectric properties of HA–BST composites sintered at 1350 °C were investigated. The HA–BST composite showed an increase in densification, Vickers hardness, Young׳s modulus and fracture toughness with maximum value as 3.42 g/cm 3, 5.01 GPa, 161.70 GPa, and 1.48 MPa m 1/2, respectively. The average grain size was decreased from 12.09 μm for a reference HA sample to 1.14 μm for the 30 wt% BST in HA–BST composites. The dielectric constant as a function of temperature and frequency tend to increase with increasing BST contents.